OPERATIONALISING A COMPETENCE MODEL OF SUPERVISION TO EMPOWER SOCIAL WORKERS AND STUDENTS IN SOUTH AFRICA - Engelbrecht, L.K. (Social Work/Maatskaplike Werk, 2004)
The purpose of this article is to demonstrate, with reference to the work of Guttman, Eisikovits & Maluccio (1988), how a competence model of supervision for social workers and students in South Africa can be operationalised. This will be done by showing the relevance of a competence model for supervision in South Africa and by explaining, with reference to outcomes-based and empowerment supervision, the rationale behind the operationalisation of the competence model. The competence model will then be conceptualised so as to provide a theoretical foundation for the model. The operationalisation of the competence model is demonstrated by defining outcomes-based supervision, explaining the relevant principles of outcomes-based supervision, defining empowerment supervision, indicating the differences between traditional and empowerment supervision, and by clarifying the relevant principles of empowerment.